The Effect of School Heads' Style in The Utilization of Online Communica-tion in Building Positive Organizational Culture - Pontanoza, Mylene B.; Callo, Eden C. (Future Science / FSH-PH Publications, 2024)
School leaders at all levels play an essential role in shaping school culture. In their daily work, principals communicate core values. Teachers instill values through their actions and words. Parents boost their spirits by visiting schools, participating in governance, and celebrating success. Communication with internal and external stakeholders is part of the school head's daily work. A day is incom-plete unless there is communication between teaching and non-teaching personnel at the school. Thus, this study used the descrip-tive correlational design to determine if the school head's communi-cation style mediates the effect of the utilization of online communi-cation in building a positive organizational culture. The respondents were the 65 school heads and 349 teachers from the 7 districts in the Division of San Pablo City. The validated survey questionnaire was used to gather the data. The data were analyzed using frequen-cy, mean, standard deviation, Pearson product-moment correlation, and multiple linear regression. The results revealed that the school heads and teachers perceived that the level of school heads' utiliza-tion of online communication, school head communication style in utilizing online communication, and building a positive organiza-tional culture were highly manifested. The test of correlation be-tween the school heads utilization of online communication in building a positive organizational culture is significant. The school heads’ utilization of online communication affects building a posi-tive organizational culture. The school head's communication style mediates the school head's utilization of online communication in building a positive organizational culture in terms of being a super-visor, and manager. The study recommends that the school should always capacitate teachers using various online platforms as inter-net communication has been a part of the system ever since the pandemic.